Firms' Export Decisions : Demand Trumps Financial Shocks - de Nicola, Francesca; Tan, Shawn W. (World Bank, Washington, DC, 2017)
This paper studies the relationship between access to credit, demand shocks, and export market adjustments using firm-level panel survey data for 24 economies in the Eastern Europe and Central Asian region. The study finds that domestic shocks to demand have a significant influence on the firm's decision to participate in international markets (extensive margin) and on the firm's share of foreign sales (intensive margin). Foreign shocks to demand only affect the firm's share of foreign sales. Conversely, the role of financial constraints on either the extensive or the intensive margin is more nuanced. The results are robust to various specifications of financial constraints and different estimation methods.